Functional and Radiological Outcome after Anatomic Coracoclavicular Ligament Reconstruction for Type III to Type V Acromioclavicular Joint Dislocation Using Semitendinous Autograft (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Acromioclavicular joint dislocation is a commonly encountered shoulder injury. Various surgical methods are available for the treatment of complete ACJ dislocation (type III to VI), however, optimal surgical treatment is still controversial. The purpose of this study was to evaluate the radiological and functional outcome of anatomic coracoclavicular reconstruction (ACCR) using semitendinosus autograft with suture augmentation for type III to V ACJ dislocation. MATERIALS AND METHODS: It was a single centered, cross sectional, observational study conducted at Department of Orthopedics and Traumatology, Dhulikhel Hospital. Twenty-three consecutive patients who underwent ACCR with semitendinosus autograft from Jan 2017 to Dec 2019 were included in the study. Patients below 18 years of age and patients with previous ipsilateral shoulder injury were excluded. The radiological outcome was assessed using coracoclavicular (CC) distance and functional outcome using DASH score and Constant score. Paired t-test and Pearson correlation were used for inferential analysis. RESULTS: Mean age of the patient was 33.83 ± 7.08 years. Mean duration of follow up was 28.17 ± 6.19 months. Mean CC distance at final follow up was 9.93 ± 1.12 mm. Mean DASH score was 5.60 ± 5.35 and mean Constant score was 88.04 ± 12.13. There were 12 (52.17%) excellent outcomes, 6 (26.08%) good outcomes, 2 (8.69%) fair outcomes and 3 (13.04%) poor outcomes based on Constant scores. CONCLUSIONS: ACCR with suture augmentation is an effective method for management of type III to V acromioclavicular joint dislocation.